Disengagement Is Not an Option: Why Repatriation of ISIS Brides Must Contain a De-radicalization Component - Emily Singh (Panoply Journal)
The relationship between a state and non-state actors can be a complicated one, even more so, when the non-state actor is allegedly affiliated with an unprecedented terrorist organization abroad. 2020 marks six years since the rise and fall of the Islamist group Islamic State (or Daesh) “Caliphate” in Iraq and Syria. A 2018 study done by the International Centre for the Study of Radicalization (ICSR) found that 41,490 citizens from 80 countries had gone to Iraq and Syria to join the terrorist organization. Of that number, researchers found that 4,640 were women. With the fall of the Caliphate, many of those women ended up in camps and are now requesting leniency and repatriation from their home countries. This paper argues that should countries choose to repatriate their female ISIS citizens (and subsequently their children), then imbued in the repatriation process ought to be a framework for de-radicalization or attitudinal modification rather than disengagement (behavioral modification).